2007
DOI: 10.1080/17477160701440521
|View full text |Cite
|
Sign up to set email alerts
|

Taste perception in massively obese and in non-obese adolescents

Abstract: Massively obese subjects have higher taste sensitivity than control subjects, especially for sucrose and salt. This can be explained, to some extent, by the influence of obesity-related metabolic disorders, which appears to be gender-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
66
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 23 publications
6
66
5
Order By: Relevance
“…Nonetheless, this association appeared independent of overall BMI. This result seems in conflict with the recent findings by Pasquet et al [16] who found a female-specific but positive association between taste sensitivity for sweet and salty tastes and the number of obesity-related metabolic disorders in a group of adolescents. This inconsistency may be ascribed to the different approach used to measure taste thresholds and to the fact that, contrary to Pasquet et al [16] study, adolescents were not considered in the present experiment.…”
contrasting
confidence: 56%
See 3 more Smart Citations
“…Nonetheless, this association appeared independent of overall BMI. This result seems in conflict with the recent findings by Pasquet et al [16] who found a female-specific but positive association between taste sensitivity for sweet and salty tastes and the number of obesity-related metabolic disorders in a group of adolescents. This inconsistency may be ascribed to the different approach used to measure taste thresholds and to the fact that, contrary to Pasquet et al [16] study, adolescents were not considered in the present experiment.…”
contrasting
confidence: 56%
“…This result seems in conflict with the recent findings by Pasquet et al [16] who found a female-specific but positive association between taste sensitivity for sweet and salty tastes and the number of obesity-related metabolic disorders in a group of adolescents. This inconsistency may be ascribed to the different approach used to measure taste thresholds and to the fact that, contrary to Pasquet et al [16] study, adolescents were not considered in the present experiment. The positive association found between higher threshold for salty taste and Mets probably is dependent, at least partially, on association between higher threshold for salty taste and hypertension as suggested by Rabin et al [29] .…”
contrasting
confidence: 56%
See 2 more Smart Citations
“…The preference for sweet and high-fat foods is frequently reported as being associated with obesity development: obese people appear to have higher preferences for sweet and fat foods and their positive response to fat becomes even greater when sweetness is added to fatty foods [2]; moreover, different authors refer to the association between sweet taste perception and body weight [3,4], with sweet detection/recognition thresholds being reported as significantly lower in morbidly obese adolescents [5].…”
Section: Introductionmentioning
confidence: 99%